Facing the demon headmaster - Cross, Gillian (Oxford Oxford University Press, 2017)
Club Purple is the place to be! The mysterious DJ Pardoman is so cool, with his ever-changing electronic mask. So when a competition is announced to unmask the DJ, everyone wants to win and find out who he is. When Dinah makes a shocking discovery she decides to investigate further, but has she fallen into a trap? Little does Dinah realize that the Demon Headmaster is about to use her in his most threatening plan yet! Great fun and just a little bit frightening, Gillian Cross's Demon Headmaster books still hold readers under their hypnotic spell. Fast-paced and full of adventure, they're impossible to resist!
Originally published: 2002.
Keywords: Demon Headmaster -- (Fictitious character) -- Juvenile fiction; Children's stories